Potentialities of drawing from observation in architectural analysis based on an analysis of the Copan building - Silva Oukawa, Carolina (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
Observation drawing can be a central tool in architectural analysis. The starting point for reflection was the analytical path of Copan Building, icon of the architecture of São Paulo, designed in the 1950 by Oscar Niemeyer. One of the motivations of that research was the lack of architectural analysis as a discipline. In music, for example, structural disciplines (Harmony, Counterpoint and Musical Perception) lead to Musical Analysis discipline, which combines reading sheet music, listening to recordings and executing the play itself. Similarly, in architecture, observation drawing made in loco can be a tool of recognition of space. In Copan analysis, besides graphical analysis (the closest one still can get from an architectural analysis procedure) successive visits to the building were made. Observation drawing proved to increase spatial perception and, above all, led to discoveries about the work.